Drug utilization, clinical and economic outcomes of patients with osteoarthritis of the hip and/or knee treated with long-term use of traditional NSAIDs, topical NSAIDs, and COX-2 inhibitors. (3rd July 2022) - Silverman, Stewart L.; Schepman, Patricia; Rice, J. Bradford; Beck, Craig G.; Johnson, Michaela; White, Alan; Robinson, Rebecca L.; Emir, Birol
Abstract: Objectives: To describe and compare baseline characteristics, healthcare and drug utilization, and negative clinical outcomes of commercially-insured patients diagnosed with OA of the hip and/or knee who initiated treatment on traditional oral NSAIDs (tNSAIDs), topical NSAIDs, or cyclooxygenase-2 inhibitors (COX-2s). Methods: A commercial claims database (1/2012–3/2017) was used to identify patients ≥18 years old, with ≥2 diagnoses of hip and/or knee OA, and ≥90 days supply of NSAIDs. Patients were assigned to cohorts based on the type of NSAID initially prescribed and observed in the 6 months before (baseline) and 36 months after (follow-up) the date of their first NSAID prescription after the first OA diagnosis. Analyses estimated baseline demographic and clinical characteristics and follow-up period drug utilization. Logistic regressions assessed the risk of gastrointestinal (GI) and acute renal failure (ARF) events. Results: tNSAIDs were the most frequently prescribed treatment. During the follow-up period, less than 15% of patients prescribed tNSAIDs switched to either COX-2s or topical NSAIDs and 37% of patients prescribed a COX-2 and 56% of patients prescribed a topical NSAID switched to tNSAIDs. GI and ARF events during the follow-up period ranged from 7.3–8.1% and 8.0–11.0%, respectively, across cohorts. The tNSAIDs and COX-2s cohorts had increased risk of both types of events relative to patients prescribed topical NSAIDs, controlling for other characteristics. Conclusions: Analyses characterize the long-term real-world utilization of NSAIDs and associated outcomes for patients with OA of the hip and/or knee. Study results highlight the likelihood of switching and the risk of negative clinical outcomes associated with long-term use.